(untitled) (European Bison Conservation Newsletter, 2009)
The reasons for sudden decline of the Ukrainian population of the European bison (Bison bonasus L.) were analyzed on the basis of historical data and current information. Described are the present status of E. bison population in Ukraine and breeding activities in zoos. Proposed are measures necessary to restore the population of this species in the country.